Coccidioides parenchymal cerebral abscess in the setting of lymphoma. Issue 1 (January 2015) - Motley, Benjamin D.; Grabowski, Matthew; Prayson, Richard A.
Abstract Coccidioides immitis is a dimorphic fungus endemic to southwestern United States of America. When symptomatic, infection usually results in a subacute respiratory infection. Disseminated coccidioidomycosis occurs in less than 1% of all cases. We report a patient with follicular lymphoma and recent travel to Arizona, who underwent resection of a cerebral Coccidioides abscess. Serology testing was negative. This case highlights the importance of clinical suspicion in patients with neurologic symptoms and travel to an endemic location.